Analisis Perawatan dan Troubleshooting Sistem Pengereman Pada Mobil Pajero Sport - Maulida, Pualam; Wibisonon Putra, Anandha Yhuto (Universitas Muhammadiyah Tangerang, 2024)
The quality of a vehicle is considered good if it is able to provide an adequate level of safety and comfort for the driver. Each car is equipped with a braking system whose job is to slow down the vehicle's speed. Therefore, care and maintenance of the braking system is very important to ensure that the system can operate optimally and return to good performance. The aim of this research is to find out troubleshooting and maintenance of the Pajero Sport car braking system. This research was conducted at PT. MITSUBISHI DIPO INTERNATIONAL PAHALA AUTOMOTIVE SERANG CITY which was carried out from February to March 2024. The research was conducted using a qualitative approach and a case study type of research. The data shows visual analysis and measuring tools for factors that cause problems with the braking system, including rust found on the piston in the master cylinder, which then causes the piston to jam. The maintenance step is to carry out cleaning using a corrosion removing fluid. The data obtained from the measurements, vibrations felt when braking, are caused by thin/uneven brake pads and wavy brake discs, so maintenance efforts include sanding/turning and replacing them with new ones.